SISTEM PAKAR PENYAKIT PADA BURUNG HIAS BERBASIS WEB MOBILE DISEASE EXPERT SYSTEM ON MOBILE WEB BASED ORNAMENTAL BIRD (Information Technology and Telematics, 2016)
Abstract The problem of disease in ornamental bird is a problem frequently found among bird lovers ornamental as well as breeders. What if not cared for properly so the bird can be stricken with the disease. Health disorders that can cause the bird is not active in Twitter, even causing death in birds on system reasoning mechanism. Mechanism of reasoning expert system using forward chaining, using knowledge representation of rule-based representation (rule base), knowledge representation model using the form of if-then (if-then) and the programs created with PHP and MySQL.The results of this research was the formation of expert system of disease on ornamental bird-based mobile web can facilitate users in doing consultations disease on ornamental birds in the way serving consists of symptoms, diseases and solutions from disease in ornamental birds. Keyword: Expert System, Ornamental Birds, Forward Chaining, PHP, MySQL.